The importance of bee products in human nutrition - Mojca KOROŠEC; Jasna BERTONCELJ (Acta Agriculturae Slovenica)
Bee products are a natural source of nutrients and biologically active compounds, which may also be found on the lists of functional ingredients. In our diets, mainly honey is used and to a lesser extent bee pollen and royal jelly. Propolis and bee venom are mainly used in apitherapy due to their therapeutic properties. Regarding the basic nutrients, honey is primarily a source of sugars, while protein and fat contents are considerable in royal jelly and pollen, which also contains dietary fiber. Bee products also contain small amounts of bioactive compounds that have antioxidant, antimicrobial, anti-inflammatory and antiviral effects. Honey is characterized by, among others, phenolic compounds, royal jelly proteins, oligosaccharides. Royal jelly contains specific fatty acids, including 10-hydroxy-2-decenoic acid, bioactive peptides, major royal jelly proteins, and pollen contains various vitamins, phenolic compounds, amino acids, unsaturated fatty acids. However, further research and clinical studies are needed to evaluate the effectiveness of bee products and to raise consumer awareness of the importance of their consumption. Honey, bee pollen and royal jelly are natural foods, which due to their composition may help to achieve the recommended daily intake of basic nutrients, and may also serve as a source of important bioactive compounds, and therefore undoubtedly belong to a balanced diet.